Education on Personal and Family Stress Management by Thinking Positively after the COVID-19 Pandemic - Dewi Nurhanifah; Muhammad Anshari (OMNICODE Journal (Omnicompetence Community Developement Journal), 2023)
Various problems caused by COVID-19 are considered to be a new source of stress for the community, namely tension, a burden for personal and family psychological conditions. This condition will gradually give a negative influence on the health of the body. Therefore, stress management needs to be known and mastered by the community to be able to maintain a healthy body. This stress management activity by thinking positively after the COVID-19 pandemic was carried out in the village of Tatah Alayung, Barito Kuala Regency. This activity was carried out in the form of socialization by visiting the village office and then residents' houses one by one. The socialization provided was in the form of tips on how to keep a positive mind during the Covid 19 pandemic and distributing and pasting posters and banners around the village. Education about personal and family stress management by thinking positively after the COVID-19 pandemic is very good and has received a good response from the community.